Dragon fruit farming - Dutt, Som (Indian Horticulture, 2019)
A field day on dragon fruit farming for aspiring farmers was held on 30 June 2018 at ICAR-IIHR-Central Horticultural Experiment Station (CHES), Hirehalli, Tumkur, Karnataka.